STUDI BIBLIKA TENTANG PAHAM HEDONISME BERDASARKAN 2 TIMOTIS 4:10 DAN IMPLIKASINYA BAGI JEMAAT GEREJA BETHEL INDONESIA JL. MOJOPAHIT BLOK SSS JEMBER - Elika Dora Br Purba (Sekolah Tinggi Teologi Duta Panisal, 2020)
Change is something that can not be dammed, because in reality times continue to change. The development of the times made a very large contribution to the changes that occurred, especially for adherents of hedonism who uphold pleasure. The development of this era brought the followers of hedonism increasingly selfish and continued to satisfy personal desires. Church and Christianity are also not spared from hedonism. The church does not realize that this understanding is rampant in the church. The church is used as a place to show off and seek recognition and even money is central to the ministry. The purpose of this determination is to find out what is meant by hedonism in 2 Timothy 4:10 and its implications for the GBI Mojopahit church. This study uses qualitative methods using theologival reflection to determine how to search, collect, process and analyze research data. The results of the study stated that hedonism really has entered and occurred in the Church. By understanding what is meant by hedonism in 2 Timothy 4:10 the congregation will be able to maintain life and even improve itself